Nitrogen oxides under pressure: stability, ionization, polymerization, and superconductivity - Li, Dongxu (Sci Rep, 2015)
Nitrogen oxides are textbook class of molecular compounds, with extensive industrial applications. Nitrogen and oxygen are also among the most abundant elements in the universe. We explore the N-O system at 0 K and up to 500 GPa though ab initio evolutionary simulations. Results show that two phase transformations of stable molecular NO(2) occur at 7 and 64 GPa, and followed by decomposition of NO(2) at 91 GPa. All of the NO(+)NO(3)(−) structures are found to be metastable at T = 0 K, so experimentally reported ionic NO(+)NO(3)(−) is either metastable or stabilized by temperature. N(2)O(5) becomes stable at 9 GPa, and transforms from P-1 to C2/c structure at 51 GPa. NO becomes thermodynamically stable at 198 GPa. This polymeric phase is superconducting (T(c) = 2.0 K) and contains a -N-N- backbone.